2021
DOI: 10.1002/adfm.202010411
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance All‐Polymer Solar Cells with a Pseudo‐Bilayer Configuration Enabled by a Stepwise Optimization Strategy

Abstract: In this work, an efficiency of 15.17% in the PBDB‐T/PYT all‐PSCs fabricated by a layer‐by‐layer (LbL) deposition technique is achieved by synergistically controlling additive dosages, which is not only higher than that (14.06%) of the corresponding bulk heterojunction (BHJ) device, but also the top efficient for all‐PSCs. Through the studies of physical dynamics and morphological characteristics, it is found that the LbL film can effectively improve optical and electronic properties, ensure exciton separation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
112
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 43 publications
1
112
0
Order By: Relevance
“…Very recently, the PCEs of all‐PSCs have been increased up to over 14% mainly via the optimization of FREA structures (Figure S1 and Table S1, Supporting Information). [ 22–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the PCEs of all‐PSCs have been increased up to over 14% mainly via the optimization of FREA structures (Figure S1 and Table S1, Supporting Information). [ 22–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high boiling point solvent additives have been introduced to modify the complex morphology of LBL device. [38] Chen et al revealed the underlying mechanism of 1,8-diiodooctane for the morphology evolution in LBL device and achieved high PCEs. [39] Nevertheless, LBL devices prepared by such methods still cannot avoid the poor stability of solvent additives.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In comparison to the bulk heterojunction (BHJ) configuration formed by the deposition of donor:acceptor (D:A) mixtures with various blending weight ratios in solution state, [5][6][7] sequential deposition of the donor and acceptor independently as two separate processing steps offers a promising route toward commercial-scale fabrication of OSCs through numerous advantages. [8][9][10][11] Each material is deposited independently, allowing the control D-A compositional gradient and optimization of vertical and lateral phase distribution Numerous previous reports on the sequential deposition (SD) technique have demonstrated that this approach can achieve a p-i-n active layer architecture with an ideal vertical composition gradient, which is one of the critical factors that can influence the physical processes that determine the photovoltaic performance of organic solar cells. Herein, a commonly used photovoltaic system comprised of PM6 as a donor and Y6 as an acceptor is investigated with respect to sequential blade-processing deposition to comprehensively explore the morphology characteristics as a function of baseplate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the pseudo-planar heterojunction (PPH) configuration, with an appropriate BHJ gradient in the middle of the active layer achieved by SD processing, [4,9] generally exhibits a slightly red-shifted absorption spectra with a higher photoabsorption rate as compared to the BHJ blend. [10] It indicates that more number of photons in the SD-processed layer can be absorbed and converted into energy (extracted charges at electrodes). [9] Apart from the optical properties, [4,9] the significant difference of BHJ and PPH morphologies influence the fundamental processes associated with the light-to-electrical energy conversion and charge collection.…”
Section: Introductionmentioning
confidence: 99%